Effects of betalain from bougainvillea (Bougainvillea spectabilis) flower bracts on the quality of pork tocino. - Fernandez, Karla Shayne Morano
Betalain is a natural pigment described as Radical Red and present in about 98.64 mg per 100 g in the red-colored Bougainvillea (B. spectabilis) flower bracts. The use of betalain as food colorant and preservative has been the focus of some studies as the negative health effects of synthetic food colorants are being addressed in food processing. The assessment of betalain as colorant and preservative in pork tocino was done in RCBD with two runs and three replications of treatments. Through a preliminary run, betalain from water extract (TBWE) was preferred by the panel than the betalain powdered bracts (TBPE). The former was used in the three formulations that served as the treatment variables. Formulation 2 (F2) had 20 g betalain/ 100 g pork meat, and Formulation 3 (F3) had 25 g betalain /100 g pork meat. F1, as the most preferred tocino (MPT), was perceived to have absence of herbal flavor with a color of Flame red. The MPT was rated as ?like very much?. During 12 days of ambient storage, the cooked MPT had significant reduction of betalain content from 67.5 mg/100 g at Day 0 to 56.61 mg/100 g at Day 8 and further reduction to 32.83 mg/100 g at Day 12. Significant (P.05) differences in Total Plate Count were observed between MPT (1.8 x 104 CFU/g at Day 0 to 3.0 x 104 CFU/g at Day 12) and Control (4.1 x 104 CFU/g at Day 0 to 2.2 x 105 CFU/g at Day 12). Psychotrophic microorganisms also showed significantly lower counts in MPT than in Control at Day0 (1.4 x 104 and 1.1 x 104 CFU/g, respectively) and at Day 12 (1.1 x 104 CFU/g and 5.3 x 105 CFU/g, respectively). These observations indicate that betalain from bougainvillea water extract when applied in pork tocino has a potential colorant function and antimicrobial activities to support stability of the product to 8 days at chilled condition. However, further studies on the preservative and antimicrobial functions to support the stability and safety of the pork tocino is needed.